Trypanosoma brucei translation initiation factor homolog EIF4E6 forms a tripartite cytosolic complex with EIF4G5 and a capping enzyme homolog - Freire, Eden R. (2014)
University of California at Los Angeles. David Geffen School of Medicine. Department of Microbiology, Immunology & Molecular Genetics. Los Angeles, California, USA.